Development of a computer-aided design software for smart garments - Kim, Sungmin (International journal of clothing science and technology, 2017)
Purpose The purpose of this paper is to develop a computer-aided design software for smart garments. Design/methodology/approach A circuit design software with graphical user interface and an automatic Arduino code generator has been developed. Findings Complex circuit design for smart garment can be performed using an intuitive graphical user interface. Sophisticated C codes for activating the smart garment can be generated without in-depth knowledge of C language and electronic devices. Research limitations/implications Circuit wiring is performed manually. Further work will be focused on the generation of an algorithm that can find the overlap-free design of complex circuit. Practical implications Smart garments with complex functions are expected to be designed more easily without in-depth knowledge of electronic circuits and computer programming. Social implications Researchers of smart garment will be able to concentrate on the actual function of smart garments rather than coding the complex C programs. Originality/value This is the first computer-aided smart garment design software that can not only design the circuit but also generate the computer codes.